The cross-border perception of Bayising (Pansheng 板升) among government officials in Ming China - Tseng, Yu-lung (Távol-keleti Tanulmányok, 2024)
The Mongol Yuan dynasty in China officially came to an end in 1368 with the withdrawal of the Mongols from the capital city Daidu (Beijing) and their retreat to the steppes. Nevertheless, a protracted series of military campaigns and conflicts between the Ming court and the Eastern Mongols, Oirat Mongols, and various other Mongol tribes continued for about 200 years. This article examines the discourse surrounding Bayising, where a group of Chinese people settled on Mongolian territory and served the Mongols during the mid-16th and early-17th centuries. The primary population of Bayising consisted of Chinese individuals who had either fled from China or were captives taken by the Mongols from China in border raids. Bayising embodies a unique interaction between China and nomadic communities in a transitional zone between the steppe and agricultural land, where conventional trading and tribute systems encountered difficulties in establishment. After the signing of the 1571 peace treaty, Bayising gradually receded from the focus of the Ming court. Through an analysis of historical documents and records, this article unveils the perspectives held by Ming officials regarding Bayising. Additionally, it probes into how these perspectives influenced Ming China’s foreign relations and national security policies concerning the Mongols. The emergence of Bayising was rooted in a distinctive historical context. Moreover, Bayising played an important role not only in shaping Sino-Mongol relations but also in facilitating cooperation between nomadic and agricultural communities in the absence of official trade channels. Neither repatriation nor military intervention proved to offer fundamental solutions to the Bayising issue in the ongoing confrontation between the Mongols and the Ming court. However, the establishment of normalised and stabilised trade, facilitated by a mutually beneficial peace treaty, emerged as a definitive solution that ultimately benefited both parties. This intricate interplay between geopolitical dynamics and cultural exchanges underscores the complexity of historical narratives, emphasizing the enduring impact of the Ming officials’ perception of the Mongols on regional stability and economic prosperity.